9514 1404 393
Answer:
16
Explanation:
There are several ways to go at this. Perhaps the simplest is to put the expression into your calculator.
__
Using the rules of exponents, you recognize ...
a^-b = 1/a^b
(a^b)^c = a^(bc)
(a^b)(a^c) = a^(b+c)
__
So, we can rewrite the expression to be ...
![\displaystyle(1)/(2)\cdot\left((1)/(2)\right)^(-5)=2^(-1)\cdot(2^(-1))^-5\\\\=2^(-1)\cdot2^((-1)(-5))=2^(-1)\cdot2^5\\\\=2^(-1+5)=2^4=\boxed{16}](https://img.qammunity.org/2022/formulas/mathematics/high-school/cjgivmjh4bmlyev054z13mjj8n6xlxg5w6.png)